Studi Literatur Analisis Sumber Daya Manusia: Sistematisasi Topik dan Arah Penelitian dari Literatur Terpilih - Dina Sarah Syahreza (Reslaj : Religion Education Social Laa Roiba Journal, 2019)
Literature studies related to human resources, but they have not been systemized in a focused topic. The way human resources are managed today is heavily influenced by the emergence of a global workforce and the increasing relevance of business analytics as an organizational strategic capability. While human resource analytics has been mostly discussed in the literature in the past decades, however, the systematic identification and classification of major topics has not been introduced. Where there is room for conceptual contributions that aim to provide a comprehensive definition of concepts and research areas related to HR analytics in the future. This study uses a systematic literature through a review process. Next, the researcher constructs the concept of human resource analytics as widely presented. There were 91 main research topics identified related to the three majors, namely HR analytics (technology and organization), application (descriptive) and diagnostic/prescriptive), and values ​​(employee values ​​and organizational values). We also speculate on an “exponential” view of HR analytics made possible by assertion of artificial intelligence and cognitive technology. This research provides a major systematization effort and future research directions to develop further studies in the field of HR analytics. Where this research offers insights to support the design of innovative analytic projects within organizations. Keywords: Human Resources, Systematization, Literature Study